SPATIO-TEMPORAL VARIATIONS OF MACRO-INVERTEBRATES IN RIFFLES AND POOLS OF MARDI AND VIJAYPUR STREAMS POKHARA, NEPAL - Pokharel, K. K. (Ecoprint: An International Journal of Ecology, 2014)
Present paper deals with the spatio-temporal variations in diversity and density of macro invertebratesin riffles and pools of the Mardi and the Vijayapur streams, Pokhara, Nepal. It was the pioneeringwork to study the biotic assemblage. Altogether 47 genera (32 from the riffles and 34 from the pools)belonging to 38 families and 12 orders were recorded during the study period. The taxa richness washigher (38 genera) in the Mardi stream than in the Vijayapur stream (30 genera). Total density at bothsites observed major peak and down fall in the spring and summer seasons, respectively. The averagetotal density during the spring peak was higher (967.42 m-2 in riffle and 652.10 m-2 in pool) at Site 1(Mardi stream) than at Site 2 (Vijaypur stream) (541.02 m-2 in riffle and 537.43 in pool). This peakwas mainly contributed by the order ephemeroptera. Ephemeroptera, diptera and trichoptera werefound predominant orders comprising 11, 8 and 8 genera, respectively. Heptagenidae, baetidae andleptophlebidae; chironomidae, ceratopogonidae and tipulidae, and hydropsychidae, psychomyidaeand polycentropodidae were dominant families among ephemeroptera, diptera and trichopterarespectively. The dominant genera were, Heptagenia Walsh, Rhithrogena Eaton and Baetis Leach;Tendipes Meigen, Culicoides Latreille and Simulium Hagen; Hydropsyche Pictet and PsychomyiaPictet; Psephenus Haldeman and Heterlimnius Hinton; Octogomphus Selys and Argia Rambur andPlanaria Girard among ephemeroptera, diptera, trichoptera, plecoptera, coleoptera, odonata andtricladida, respectively. The lower taxa richness at Site 2 having urban influence reflects theperturbation of stream environment due to urbanization, industrialization and application of inorganicfertilizers and pesticides in the agricultural lands, which needs regular ecological monitoring andmeasures to control further deterioration. DOI: http://dx.doi.org/10.3126/eco.v20i0.11442 ECOPRINT An International Journal of Ecology Vol. 20, 2013 Page: 61-70